Happy ageing by trusting our gut microbes - Anusha, Jayaraman; Pettersson, Sven * (Elsevier, 2022)
The human gut microbiota comprises of trillions of micro-organisms in the gut some which secrete metabolites that play a pivotal role in supporting optimal body and organ functions. These dynamic and malleable gut microbes share a bidirectional relationship with their hosts that supports health in an age- and sex-dependent manner. Disruption of the gut microbiota or decrease in their diversity and richness due to unhealthy changes in lifestyle, diet or social disconnection, always results in unwanted outcomes on the host health which fuel chronic disease symptoms including neurodegenerative diseases. Thus, impairment of gut microbiota composition, results in organ decline that accelerates an individual's biological ageing. Here we review evidence supporting the bidirectional relationships between the gut microbiota and biological ageing.